(untitled) (Journal of actual problems of jurisprudence, 2019)
The article discusses the features of the patient’s position as a recipient of medical services; issues of legal regulation of the provision of medical services, contractual relations. It also considers ways to improve legislation in the provision of medical services. There are several reasons for this and it is difficult to separate them from each other – this is an increase in the number of medical errors, and an increase in the legal awareness of the population and, as a consequence, an increase in the number of lawsuits and required amounts of compensation, it is also the loyalty of the courts to the victims and the increasing compensation amounts. On the one hand, the listed judicial aspects of the activities of medical institutions can be viewed as factors affecting the degree of realization of the risks of providing low-quality services. But, in my opinion, they should be considered as a separate group of risks, since the phenomena underlying them, among other things, will lead to the presentation of unfounded excessive claims to medical organizations in cases where their fault is absent. In this case, the implementation of a risk factor can lead to problems at the clinic and thus goes from the category of risk factors to the category of hazards. This means that judicial practice requires special attention when organizing a risk management system. Key words: health care, finance, risk, court of justice, medical services, legislation, patient, health, contractual relations.